1995
DOI: 10.1111/j.1469-8137.1995.tb01810.x
|View full text |Cite
|
Sign up to set email alerts
|

Tansley Review No. 82. Strategies of arbuscular mycorrhizal fungi when infecting host plants

Abstract: summary Arbuscular mycorrhizal (AM) fungi are ancient Zygomycetes, thought to have colonized the first land plants; today, they are associated with the roots of about 80% of plant species. The symbiosis they form is potentially valuable not only for developmental programmes based on low‐input agriculture, but also as a complex experimental model, where both fungal and host plant growth are regulated. Here we review some recent progress m the area of cell and molecular biology of arbuscular mycorrhizas. Particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
135
1
6

Year Published

1998
1998
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 251 publications
(149 citation statements)
references
References 96 publications
(101 reference statements)
7
135
1
6
Order By: Relevance
“…In some cases, an induction of defence responses was detected at early stages of root colonization followed by suppression at later stages of the symbiosis (Spanu et al, 1989 ;Lambais & Mehdy, 1993 ;Volpin et al, 1994Volpin et al, , 1995 ; in other cases, there was no major change in the expression of plant defence-related genes in response to mycorrhizal root colonization (Franken & Gna$ dinger, 1994 ;Blee & Anderson, 1996). The overall impression from these studies was that plant defencerelated genes are only weakly or transiently expressed in response to infection by AM fungi (for reviews, see Bonfante & Perotto (1995), Gianinazzi-Pearson et al (1996)). By contrast, numerous studies have demonstrated that, in pathogenic interactions, distinct changes in plant gene expression take place, many of which have presumed protective functions.…”
Section: mentioning
confidence: 97%
See 1 more Smart Citation
“…In some cases, an induction of defence responses was detected at early stages of root colonization followed by suppression at later stages of the symbiosis (Spanu et al, 1989 ;Lambais & Mehdy, 1993 ;Volpin et al, 1994Volpin et al, , 1995 ; in other cases, there was no major change in the expression of plant defence-related genes in response to mycorrhizal root colonization (Franken & Gna$ dinger, 1994 ;Blee & Anderson, 1996). The overall impression from these studies was that plant defencerelated genes are only weakly or transiently expressed in response to infection by AM fungi (for reviews, see Bonfante & Perotto (1995), Gianinazzi-Pearson et al (1996)). By contrast, numerous studies have demonstrated that, in pathogenic interactions, distinct changes in plant gene expression take place, many of which have presumed protective functions.…”
Section: mentioning
confidence: 97%
“…In other mycorrhizal systems, both stimulation and suppression of plant defence responses have been reported (for reviews, see Bonfante & Perotto (1995), Gianinazzi-Pearson et al (1996)). Early induction followed by suppression of plant defencegene expression has been demonstrated for mycorrhizal beans (Lambais & Mehdy, 1993).…”
Section: Mycorrhizal Colonization Of Bean Roots Has No Effect On Planmentioning
confidence: 99%
“…Mosse & Hepper (1975) considered it ' interesting (…) that finely branched, thin-walled structures very similar to arbuscules can develop outside the root '. However, to the best of our knowledge, there has been no further investigation into these structures which seem to be, paraphrasing Bonfante & Perotto (1995), a dead-end in the growth of AM fungi outside the plant.…”
Section: mentioning
confidence: 99%
“…They are greatly extended apices of the fungal colony within root tissues (Gianinazzi-Pearson et al, 1995), and considered to be a dead-end in the growth of AM fungi inside the plant (Bonfante & Perotto, 1995). Owing to the increased contact surface area, and the fact that almost no physical barrier remains between plant and fungal plasmamembranes at the arbuscular branch level, arbuscules have been proposed as the preferential site for plant-fungal nutrient exchange (Bonfante-Fasolo, 1984 ;Smith & Smith, 1990).…”
Section: mentioning
confidence: 99%
“…Genotypic and environmental factors influence whether an interaction results in extensive infection of cortical cells or, alternatively, in aborted or limited infection (Bonfante & Perotto, 1995). These phenotypic differences in infection might be related to differences in host defence-related gene expression.…”
Section: mentioning
confidence: 99%